Necessary lies [large type] - Chamberlain, Diane, 1950- (Thorndike Press, 2013)
After losing her parents, fifteen-year-old Ivy Hart is left to care for her grandmother, older sister and nephew as tenants on a small tobacco farm. As she struggles with her sister's mental illness and her own epilepsy, Ivy realizes they might need more than she can give. Jane Forrester, Grace County's newest social worker, doesn't realize just how much her help is needed. Drawn in by the Hart women, she begins to discover the dark secrets of the small farm.